Silver-Russell syndrome (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Silver-Russell syndrome is clinically and genetically a heterogeneous disorder. In most of the cases, etiology is unknown, only in 10% cases defect in chromosome 7 is identified. It bas distinctive facial features and asymmetric limbs. Most predominant symptom is growth failure. A case of Silver-Russell syndrome reported here who presented with growth failure, hemihypertrophy ofleft side oftbe body, dysmorphic facial profile and difficulty in speech. Counseling was done with the parents regarding the etiology, progression and outcome of the disease.